Analysis of error sources in L2 written English by Indonesian undergraduate students - Burhansyah, Burhansyah (Studies in English language and education, 2019)
This study investigates second language learners’ production in writing, aiming to understand common problems the learners frequently have with English. The study focuses on the analysis of errors in 100 essays written by 50 Indonesian undergraduate students of English, which is aimed at identifying the commonly occurring errors, classifying them according to a linguistic category, and explaining the causes of the occurring errors. The study shows that a large number of the occurring errors resulted from intralingual sources, the proportion of which account for more than 60% of the total errors. The results conform to a number of earlier studies in this research field which concluded that the majority of errors L2 learners make stem from intralingual interference. Another possible explanation for the phenomena is that because the subjects participating in this study are university students majoring in English, they had at least mastered the basics of English when entering university. As a result, they are more likely to make fewer interlingual errors than students at elementary level who tend to rely more on their native language when dealing with the aspects of the target language which they have not yet mastered.